Embryo-fetal safety evaluation of ondansetron in rats - Reis, Ana Carolina Casali [UNESP]; Jorge, Bárbara Campos [UNESP]; da Silva Moreira, Suyane [UNESP]; Stein, Júlia [UNESP]; Perdão, Carolina Barizan [UNESP]; de Matos Manoel, Beatriz; Arena, Arielle Cristina [UNESP] (Wiley, 2023)
Background: Ondansetron is a 5HT3 receptor antagonist, used to mitigate the effects of nausea and vomiting after chemotherapy or surgery. Since nausea and vomiting are common experiences during the first trimester of pregnancy, this antiemetic has been the main drug used during this period. Methods: To evaluate the effects of ondansetron on the embryo-fetal development, which are still very contradictory, pregnant rats were exposed to therapeutic doses of ondansetron (1.7 or 2.5 mg/kg) daily, from gestational day (GD) 6 to 15. Results: No clinical signs of toxicity were observed in dams during the treatment. Although the hemato-biochemical parameters were similar among the groups, histological changes, as well as a reduction in the weight of kidney were found in the treated dams. After fetal examination, no visceral and skeletal abnormalities were observed in treated fetuses. Conclusion: In conclusion, therapeutic doses of ondansetron have low teratogenic potential in rats. These data provide important information about the drug safety during pregnancy.
Keywords: kidney; nausea and vomiting; organogenesis; rats; safety; teratogenicity